EFFICACY OF STUDYING AS PREDICTOR OF HIGHER EDUCATION QUALITY: THE CASE STUDY OF FACULTY OF AGRICULTURE - Mutavdžić, Beba; Babić-Kekez, Snežana; Novković, Nebojša; Novaković, Tihomir (Economics of Agriculture, 2016)
Creation of education policy starts at, among other things, the vision of education systems quality. Comprehension of the concept of quality is multifaceted, so in higher education the holistic, multidisciplinary approach is the most appropriate for it acknowledges different segments of quality. One of those is measuring effciency of studying based on input: type of high school, and the success achieved in high school, what is the goal of this research. Applying regression analysis on a sample of 1,114 subjects, students of the Faculty of Agriculture, the influence of success in high school to the average years of study and accomplished success during studies had been explored. For all courses, defning the influence of success in high school to the average years of study had negative coeffcient of correlation, which means that by increasing the number of points earned in high school there is a decrease of average years of study (sum coeffcient, r = -0.23). Due to the fact that the problem is in the uneven criteria of evaluation and assessment at high school level of education in Serbia, especially between high schools and vocational schools, results of this research are pointing out the necessity for equalization and compatibility of all elements in education system, and of bringing national outcomes of education at all levels and national qualifcation frames.